Cofactor‐induced reversible folding of Flavodoxin‐4 from Lactobacillus acidophilus. (30th July 2015) - Dutta, Samit Kumar; Serrano, Pedro; Geralt, Michael; Axelrod, Herbert L.; Xu, Qingping; Lesley, Scott A.; Godzik, Adam; Deacon, Ashley M.; Elsliger, Marc‐André; Wilson, Ian A.; Wüthrich, Kurt
Abstract: Flavodoxins in combination with the flavin mononucleotide (FMN) cofactor play important roles for electron transport in prokaryotes. Here, novel insights into the FMN‐binding mechanism to flavodoxins‐4 were obtained from the NMR structures of the apo‐protein from Lactobacillus acidophilus (YP_193882.1) and comparison of its complex with FMN. Extensive reversible conformational changes were observed upon FMN binding and release. The NMR structure of the FMN complex is in agreement with the crystal structure (PDB ID:3EDO ) and exhibits the characteristic flavodoxin fold, with a central five‐stranded parallel β–sheet and five α‐helices forming an α/β‐sandwich architecture. The structure differs from other flavoproteins in that helix α2 is oriented perpendicular to the β‐sheet and covers the FMN‐binding site. This helix reversibly unfolds upon removal of the FMN ligand, which represents a unique structural rearrangement among flavodoxins.